The Nigerian rice economy : policy options for transforming production, marketing and trade - Gyimah-Brempong, Kwabena; Johnson, Michael, 1963-; Takeshima, Hiroyuki (University of Pennsylvania Press, Inc., 2016)
"In The Nigerian Rice Economy the authors assess three options for reducing this dependency - tariffs and other trade policies; increasing domestic rice production; and improving post-harvest rice processing and marketing - and identify improved production and post-harvest activities as the most promising. These options however, will require substantially increased public investments in a variety of areas, including research and development, basic infrastructure (for example, irrigation, feeder roads, and electricity), and rice milling technologies."